Significance of Serum mtDNA Concentration in Lung Injury Induced by Hip Fracture. Issue 1 (July 2015) - Gan, Li; Chen, Xiaobin; Sun, Tiansheng; Li, Qi; Zhang, Ruhui; Zhang, Jianzheng; Zhong, Jianfeng
Abstract : ABSTRACT: Acute lung injury is the most serious and fatal complication of the elderly patients with hip fracture, but the mechanisms are unknown. Recent studies demonstrated the mitochondrial DNA (mtDNA) release was associated with lung injury after trauma. This study aimed to examine the differential release of mtDNA between younger and elderly rats suffering from hip fracture and to investigate the possible mechanism of mtDNA in the lung injury induced by hip fracture. In the first part of the study, we investigated the effects of hip fracture on the rats. The elderly and younger rats, respectively, received hip fracture operations. The degree of lung injury was evaluated, toll-like receptor 9 (TLR9) and nuclear factor kappa B (NF-κB) were determined using Western blot, and mtDNA were analyzed by fluorescent quantitative polymerase chain reaction. In the second part of the study, we investigated the effects of mtDNA on the rats. The elderly and younger rats directly received intravenous injections with mtDNA. After 24 h, the specimens were collected and detected as the first part. Hip fracture resulted in significant mtDNA release, TLR9 and NF-κB p65 expression, and lung injury in the rats. Meanwhile, the mtDNA injection could indirectly induce lung injury. Compared to the younger ones, the elderly rats suffered more serious lung injury after hip fracture and mtDNA injection. These results suggest that the lung injury induced by hip fracture may be involved with the mtDNA release and its TLR9/NF-κB pathway.